ANALISIS HOMOGENITAS SELF COMPACTING MORTAR MENGGUNAKAN SERAT POLYPROPYLENE BERDASARKAN KECEPATAN PERAMBATAN GELOMBANG ULTRASONIK (UPVM) - Faqih Ma’arif; Slamet Widodo; Agus Santoso (Universitas Negeri Yogyakarta, 2011)
Nowadays, Non Destructive Tests have been applied in many qualityevaluations of existing concrete structures. One of the Non Destructive Tests (NDT)is based on Ultrasonic Pulse Velocity (UPV). The use of UPV method among othersare to estimate the strength of concrete, to detect the presence of crack, to measurethe homogeneity of concrete, the thickness of concrete slab, and also to estimate thediameter of the embedded steel reinforcement. The NDT technique will apply on thisresearch. This research used 24 cylinder test samples in four groups, which werereference cylinder (SR), cylinder-1 (S-01) with 0.5 kg/m3 of fibers, cylinder-2 (S-02)with 1.0 kg/m3 of fibers and cylinder-3 (S-03) with 1.5kg/m3 of fibers. Those cylinderswere of 150 mm in diameter and 300mm in height. The Ultrasonic Pulse Velocity(UPV) test was conducted with direct test method. The data are then analyzed usingstatistical program. The test result showed that the addition of polypropylene fibersoptimum and pulse velocity were of 1kg/m3 and 3,19km/s respectively. The increasepulse velocity transmitter higher on variation of fibers 1kg/m3 is 9,12% in comparisonto reference cylinder. The statistical test indicated that the signifinance value (2-tailed test) is homogeneity sample. This means that the ultrasonic pulse velocitymethod can used to knowing of homogeneity self compacting mortar using fibers.Keyword: Homogeneity, polypropylene, Ultrasonic pulse velocity Method